High-resolution mapping of significant wave heights in the Northeast Pacific and Northwest Atlantic using improved multi-source satellite altimetry fusion method - Yang, Hongbin; Liang, Bingchen; Gao, Huijun; Shao, Zhuxiao (Frontiers in Marine Science, 2024)
Significant wave height (SWH) is an important parameter to reflect wave state, which is of great significance in ocean engineering. However, the current wave observation methods have limitations in capturing wave field data with high spatial resolution. In this study, to generate the SWHs field over the Northeast Pacific and Northwest Atlantic, multi-source satellite altimeter data (CRYOSAT-2, SARAL, JASON-3, SENTINEL-3A, SENTINEL-3B, HY-2B and CFOSAT) are fused with a spatial resolution of 0.125° x 0.125° and a temporal resolution of 1 day. We employ the Inverse Distance Weighting (IDW) method and the IDW-based spatiotemporal (IDW-ST) method for data fusion. The fusion results exhibit a consistent spatial distribution characteristic, but the results of the IDW method display the visible trajectory. Moreover, the IDW-ST method, which incorporates time factors, shows great agreement between the fused SWH and buoy data. However, when the water depth change near the grid point has a great influence on the fusion, the complexity of bathymetric topography makes the traditional two-dimensional spatial fusion methods inadequate. Therefore, an improved method is proposed based on the IDW-ST fusion method, which introduces the water depth factor and significantly enhances fusion accuracy in regions where bathymetric variations greatly affect fusion results. The proposed method can be used to generate reliable SWH fields, especially in complex bathymetric topography conditions, and provide significant support for marine infrastructure design, ocean energy utilization and marine disaster protection.